Allie, first at last - Cervantes, Angela (Scholastic Press, 2016)
Born into a family of over-achievers, fifth-grader Allie Velasco has never finished first in anything, and lately things have been going badly: her science project is ruined by a well-meaning student, her former best friend is hanging out with another girl--but now she is determined to win the Trailblazer contest with a photographic presentation about her great grandfather, the first Congressional Medal of Honor winner from their town.